FILOSOFI HUMOR DAKWAH - fahriansyah fahriansyah (UIN Antasari Banjarmasin, 2020)
The phenomenon of the use of Humor in Da'wah Bil Lisan is a sign that the attraction of da'wah objects to the exposure of oral offerings in da'wah is influenced by the presence of humorous insertions in each Dakwah Bil Lisan ( Da'wah Oral ) , but in reality the use of humor in Da'wah Bil Lisan has a very high level of complexity due to the ability of lecturers in producing very limited humorous offerings which are limited by the existence of values that must be brought as a manifestation of the purpose of Da'wah Islamiyah. Therefore, a philosophical understanding of humor is needed because of the harmony between the purpose of da'wah and the purpose of humor presented in lectures (Da'wah Bil Lisan ).